FAKTOR PENYEBAB PERKAHWINAN TANPA KEBENARAN DI LUAR NEGARA: SATU KAJIAN DI MAHKAMAH RENDAH SYARIAH MUAR - Mohd Nor, Amir Husin (Jurnal Syariah, 2006)
The objective of the article is to examine and determine the reasons behind the action taken by the couple to contract their marriage outside Malaysia. The research is conducted at the Syariah Court of Muar which focused on the cases filed in 2003. The result shows that there are three main factors contributed to this alarming phenomenon namely; the family, nationality and legal factors.